(untitled) (Journal of Nepal Geological Society, 2001)
Sedimentological study has revealed vertical and lateral sedimentary facies changes of the Plio-Pleistocene Kathmandu Basin Group in the southern part of the Kathmandu Valley, Nepal. The field observation and analyses of XRD, carbon content. C/N ratio and diatom fossils indicate that depositional environments of muddy sediments in this area can be classified into four categories: i) open lacustrine, ii) shallow lacustrine. iii) swamp-shallow lacustrine, and iv) environment strongly affected by fluvial system. Distributions of sedimentary facies in Lukundol, located in the southern margin of the Kathmandu Basin, show that fluvial facies dominant sequence in the Tarebhir Formation changed to a marginal lacustrine facies in the Lukundol Formation at 2.8 Ma, and a fluvial facies in the ltaiti Formation developed at 1 Ma following the deposition of the Lukundol Formation. In the area 5 km north of Lukundol, an open lacustrine facies in the Kalimati Formation dominated during the deposition of the Lukundol and Itaiti formations. The relation between the vertical sedimentary facies changes and palaeoclimate estimated from clay mineral crystallinity indicates: (1) the termination of fluvial facies dominant sequence at 2.8 Ma corresponds to the time where a wet climate turned to a drier climate, (2) fluvial environments developed under the wet climate and swamp-shallow lacustrine environments expanded under the dry climate during the deposition of the Lukundol Formation.